(untitled) (CIPEEX, 2025)
Introduction: Imaging is an area in growing expansion within Biomedicine, ranging from traditional diagnostic imaging exams to advanced technological innovations in digital analysis. Participation in this sector is supported by Brazilian legislation and is strengthened by scientific advances, which demand qualified professionals to work in hospitals, clinics and research centers. Objective: To analyze the role of biomedical professionals in bioimaging. Methodology: A narrative-type literature search was carried out between June and August 2025, using the following keywords: Biomedicine (AND); (AND) Bioimaging (OR) Imaging. The searches were carried out in the databases of PubMed, SciElo, Lilacs and CAPES Journals, including complete scientific articles published in Portuguese and English, which addressed professional performance in clinical imaging, digital pathology and image analysis in research. Results: The reviewed studies demonstrate that the current legislation guarantees the presence of biomedical professionals in imaging services, expanding their performance in hospitals and clinics. In addition, international literature highlights the relevance of biomedical in the transition to digital pathology, where they perform functions from sample preparation to the interpretation of images with technological support. In the scientific environment, the role of the imaging analyst is highlighted as essential for the acquisition, processing and analysis of visual data, ensuring the quality of research results. Conclusion: The biomedical is essential in multifaceted and strategic performance, uniting clinical practice, technological innovation and science. Their participation strengthens diagnosis, contributes to advances in health and reinforces the need for continuous training.